Dead masters : mentoring and intertextuality in Samuel Johnson - Lee, Anthony W. (Lehigh University Press ; Rowman & Littlefield Pub. Group, 2011)
"Dead Masters examines the dual issues of mentoring and intertextuality as an integrated phenomenon. Through a series of fresh and novel readings of Johnsonian and Boswellian texts, the book further advances our awareness of the formal complexities of Johnson's writings and the psychological substratum from which they issue"--